(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the pedagogical significance of the historical comparative method as a vital tool in history education. It emphasizes how comparing historical events, periods, and figures helps students move beyond rote memorization of facts and dates toward a more holistic understanding of history. Through comparative analysis, students develop critical thinking skills, learn to evaluate sources, and comprehend the cause-and-effect relationships among socio-political, economic, and cultural phenomena. The method is especially crucial in training future history educators, enabling them to teach history as an interconnected and dynamic process. The article also highlights the method’s role in fostering analytical reasoning and promoting meaningful engagement with historical content across local and global contexts.